ZAMONAVIY XIRURGIYADA ASEPTIKA VA ANTISEPTIKA TAMOYILLARI: NAZARIY ASOSLAR VA AMALIY AHAMIYATI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This scientific article comprehensively examines the theoretical foundations, historical development, and practical significance of aseptic and antiseptic principles in modern surgery. Asepsis and antisepsis play a crucial role in preventing surgical infections, reducing postoperative septic complications, and ensuring patient safety. The article analyzes modern sterilization and disinfection methods, contemporary antiseptic agents, and the responsibility of medical personnel in maintaining effective infection control.